Image-based sexual abuse: a study on the causes and consequences of non-consensual nude or sexual imagery - Henry, Nicola (Routledge critical studies in crime, diversity and criminal justice, 2021)
Image-based sexual abuse: beyond "revenge pornography" -- Victim-survivor experiences of image-based sexual abuse -- The harms of image-based sexual abuse / with Erika Rackley and Nicola Gavey -- Image-based sexual abuse perpetration: power and control -- Visual criminality: a theory of image-based sexual abuse -- The missing culture of consent: shifting social norms on image-sharing, sexual autonomy and harm -- Seeking justice for victim-survivors of image-based sexual abuse / with Erika Rackley -- Preventing image-based sexual abuse: ethics, consent and respectful relationships.